Shuttle Diplomacy Indonesia sebagai Upaya Penyelesaian Konflik Thailand-Kamboja - Khalda Fadlah Fadhilah (Jurnal Kajian Wilayah, 2020)
This research aims to determine how Indonesia uses Shuttle Diplomacy in resolving conflicts between Thailand and Cambodia. Indonesia's role in this conflict is as a third party that acts as a mediator between two parties in conflict using the shuttle diplomacy method. This research will describes the background of the Thailand-Cambodia conflict, the role and how the shuttle diplomacy is used by Indonesia in resolving the fatigue conflict, the factors from Indonesia in choosing shuttle diplomacy, and the obstacles used by Indonesia when it becomes The mediator uses shuttle diplomacy in resolving the regional conflict between Thailand and Cambodia. This research uses qualitative methods with descriptive research type. Researchers obtained data by conducting literature studies. Researchers use foreign policy theory with the concept of national interest to see and understand the reasons for Indonesia to intervene in the resolution of the conflict between Thailand and Cambodia.